The Relationship Between Food Acceptability and Intake on Morning Meal Leftovers in Pediatric Patients - Trihandayani, Yuliana; Nurhartanto, Adhi; Jalaludin, Asep (Genius Journal, 2026)
Introduction: Childhood malnutrition remains a significant public health concern, and adequate nutritional intake during hospitalization is essential to support recovery and growth in pediatric patients. Hospital food services are required to provide nutritionally adequate and acceptable meals; however, food waste among hospitalized children, particularly during breakfast, remains a persistent problem. High levels of leftover food may indicate low food acceptability and inadequate food intake, which can hinder the fulfillment of children’s nutritional needs. Food acceptability, influenced by sensory characteristics and eating habits, plays an important role in determining food consumption among pediatric patients. Therefore, evaluating the relationship between food acceptability, food intake, and breakfast food waste is crucial to improve the effectiveness of hospital nutrition services for children. Objective: Child nutrition issues, such as wasting and stunting, remain a serious challenge, especially in developing countries. Optimal nutrition in hospitals is important to support children's growth and recovery. This study aims to analyze the relationship between acceptability and food intake to morning food waste in pediatric patients at Santa Anna Hospital. Method: This study used a descriptive quantitative method with a cross-sectional approach. A sample of 30 inpatient pediatric patients was taken purposively. Acceptability was measured using an organoleptic assessment form, while food intake was measured using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were analyzed univariately and bivariately using the chi-square test. Result: The results showed that 86.7% of children liked the morning meal menu, 96.6% had sufficient to good intake, but 53.3% still left food in large quantities. There was a significant relationship between acceptability and food waste (p = 0.009), and between food intake and food waste (p = 0.001). Conclusion: The higher the acceptability and food intake, the less food leftovers left by pediatric patients.. Conclusion: The results of this study emphasize the importance of improving the quality of nutrition services, including menu improvement, presentation, and patient companion education to reduce food waste and support optimal recovery of pediatric patients. Introduction: Childhood malnutrition remains a significant public health concern, and adequate nutritional intake during hospitalization is essential to support recovery and growth in pediatric patients. Hospital food services are required to provide nutritionally adequate and acceptable meals; however, food waste among hospitalized children, particularly during breakfast, remains a persistent problem. High levels of leftover food may indicate low food acceptability and inadequate food intake, which can hinder the fulfillment of children’s nutritional needs. Food acceptability, influenced by sensory characteristics and eating habits, plays an important role in determining food consumption among pediatric patients. Therefore, evaluating the relationship between food acceptability, food intake, and breakfast food waste is crucial to improve the effectiveness of hospital nutrition services for children. Objective: Child nutrition issues, such as wasting and stunting, remain a serious challenge, especially in developing countries. Optimal nutrition in hospitals is important to support children's growth and recovery. This study aims to analyze the relationship between acceptability and food intake to morning food waste in pediatric patients at Santa Anna Hospital. Method: This study used a descriptive quantitative method with a cross-sectional approach. A sample of 30 inpatient pediatric patients was taken purposively. Acceptability was measured using an organoleptic assessment form, while food intake was measured using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were analyzed univariately and bivariately using the chi-square test. Result: The results showed that 86.7% of children liked the morning meal menu, 96.6% had sufficient to good intake, but 53.3% still left food in large quantities. There was a significant relationship between acceptability and food waste (p = 0.009), and between food intake and food waste (p = 0.001). Conclusion: The higher the acceptability and food intake, the less food leftovers left by pediatric patients.. Conclusion: The results of this study emphasize the importance of improving the quality of nutrition services, including menu improvement, presentation, and patient companion education to reduce food waste and support optimal recovery of pediatric patients.